REPRESENTATION OF CORPOREALITYI-BOHDAN TOMENCHUK’S POETRY(on the base of a book «Figures. Silhouettes») - Деркачова, О. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article dealsto the research of corporeality in Bohdan Tomenchuk’s poetry. The body, feeling of body, external body are analyzing. The poems with self-corporeality and other corporeality (native body, body of enemy, national corp, heroic corp) are researching. The alive body, body in trauma, death body are examine. Determined that the most important is connection the soul and body, offering own body for Motherland. There are two worlds: the world of love (for existence of her and him) and the world of trauma (war, struggle) in which there are heroes from past and figures-symbols.